2021
DOI: 10.1007/s10853-021-05926-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity and enhanced thermoelectric performance of SnTe bilayer

Abstract: Tin chalcogenides (SnS, SnSe and SnTe) are found to have improved thermoelectric properties upon the reduction of their dimensionality. Here we found the tilted AA + s stacked twodimensional (2D) SnTe bilayer as the most stable phase among several stackings as predicted by the structural optimization and phonon transport properties. The carrier mobility and relaxation time are evaluated using the deformation potential theory -these are found to be relatively high due to the high 2D elastic modulus, low deforma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 76 publications
0
4
0
1
Order By: Relevance
“…Very interesting predictions were obtained from a theoretical analysis of SnTe bilayers in which, due to the bi-layer structure, in the authors' opinion, it was possible to realize the two-dimensionality of the electronic transport of this threedimensional compound [123]. They performed ab initio calculations combined with the Boltzmann transport theory to study the lattice dynamics, structural, electronic, and thermoelectric properties of the 2D SnTe bilayer.…”
Section: Layered Monochalcogenides MX (Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Very interesting predictions were obtained from a theoretical analysis of SnTe bilayers in which, due to the bi-layer structure, in the authors' opinion, it was possible to realize the two-dimensionality of the electronic transport of this threedimensional compound [123]. They performed ab initio calculations combined with the Boltzmann transport theory to study the lattice dynamics, structural, electronic, and thermoelectric properties of the 2D SnTe bilayer.…”
Section: Layered Monochalcogenides MX (Mmentioning
confidence: 99%
“…In addition, the authors concluded that their results show that the [CoO 2 ] subsystem is responsible for the transport of charge carriers in Ca 3 Co 4 O 9 , that is, confirms the conclusion about the decisive role of layering in the electron transport of the Ca 3 Co 4 O 9 compound. The difference in the features of magnetic ordering in single crystals [125] and in polycrystals [123] indicates that anisotropic magnetic ordering is averaged in samples. Hira et al [132] report on the electrical, magnetic, and magnetotransport properties of Ca 3−2x Na 2x Co 4−x Mo x O 9 (0 ⩽ x ⩽ 0, 15) samples with Na and Mo dual doping.…”
Section: Layered Oxides Ca 3 Co 4 Omentioning
confidence: 99%
“…All four of the materials have very low lattice thermal conductivity. We also found the different lattice thermal conductivity along the armchair and zigzag directions [136] .…”
Section: V-v族化合物mentioning
confidence: 57%
“…空间分辨的dI/dV spectra(右图) [123] ; (f) 横向SnS存储器件(通道长度L = 4 µm, 从-5.5 V循环到5.5 V)在不同栅极电压V g 下 的I-V磁滞曲线 [129] ; (g) 采用迭代法(实线)和单模弛豫时间近似法(single-mode relaxation time approximation,SMRTA)(虚线)计 算了Ⅳ-Ⅵ族单层膜的晶格导热系数随温度的变化. 四种材料的晶格导热系数都很低, 同时沿扶手椅和之字形方向的晶格导热系 数不同 [136] ing. Spatially resolved dI/dV spectra (right panels) obtained along the two arrows in the image on the left [123] .…”
Section: V-v族化合物unclassified
“…In this work we study the finite-temperature anharmonic phonons and the associated thermodynamic properties along with the LTC of the two-dimensional (2D) zirconium disulphide (ZrS2) monolayer (ML), which is a typical 2D transition metal dichalcogenide (TMDC) that has been successfully synthesized [32][33][34][35]. Lowering the dimensionality and nano-structuring are reported to play major roles in suppressing the LTC that leads to an enhancement in the figure of merit (ZT) [36][37][38][39][40]. By using the conventional Boltzmann transport equation (BTE) within the relaxation time approximation (RTA), the LTC was predicted to be significantly low for the ZrS2 ML as compared to other similar 2D compounds [21], which is an important feature in the TE efficiency enhancement and device applications.…”
Section: Introductionmentioning
confidence: 99%